1992
DOI: 10.1113/jphysiol.1992.sp019396
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐dependent ionic currents in dissociated paratracheal ganglion cells of the rat.

Abstract: SUMMARY1. Conventional whole-cell voltage-clamp technique was used to study the electrophysiological and pharmacological properties of voltage-dependent Na', K+ and Ca21 channels in parasympathetic neurones enzymatically dissociated from the paratracheal ganglia of rat trachea. The voltage-dependent Na+, K+ and Ca2+ currents (INa' IK and ICa) were separated by the use of ion subtraction and pharmacological treatments.2. INa was activated by a step depolarization more positive than -50 mV and fully activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
3
6
1
Order By: Relevance
“…Neuronal Ca 2+ channels have been shown to be classified into two subtypes including low‐voltage‐activated (LVA) and high‐voltage‐activated (HVA) Ca 2+ channels. However, as previously described (Aibara et al , 1992), the LVA Ca 2+ channel current was not observed in the present preparation (not shown). Therefore, the effects of ACh on HVA 7 Ca evoked by a depolarizing step pulse from a holding potential (V H ) of ‐ 50 mV to + 20 mV were examined.…”
Section: Resultssupporting
confidence: 84%
“…Neuronal Ca 2+ channels have been shown to be classified into two subtypes including low‐voltage‐activated (LVA) and high‐voltage‐activated (HVA) Ca 2+ channels. However, as previously described (Aibara et al , 1992), the LVA Ca 2+ channel current was not observed in the present preparation (not shown). Therefore, the effects of ACh on HVA 7 Ca evoked by a depolarizing step pulse from a holding potential (V H ) of ‐ 50 mV to + 20 mV were examined.…”
Section: Resultssupporting
confidence: 84%
“…The procedure for obtaining dissociated paratracheal ganglion neurons is similar to that described elsewhere (Aibara et al ., 1992; Ishibashi et al ., 2001). Briefly, the paratracheal ganglia were rapidly removed from the trachea of 2‐week‐old Wistar rats under ether anaesthesia, and the rats were subsequently killed by exsanguination.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, there is still surprisingly little information about the electrophysiological properties of tracheal ganglion neurones, given the important role of such neurones in the regulation of airway tone and secretion. Electrophysiological investigations have been made of paratracheal neurones of the ferret (Baker et al, 1986;Cameron and Coburn, 1984;Coburn, 1984Coburn, , 1987Coburn and Kalia, 1986), cat (Mitchell et al, 1987) and, most extensively, of the rat (Allen and Burnstock, 1990;Aibara et al, 1992;Reekie and Burnstock, 1992).…”
mentioning
confidence: 99%